KESESUAIAN PEMBELAJARAN EKONOMI ISLAM DI PERGURUAN TINGGI DENGAN KEBUTUHAN SDM PADA INDUSTRI KEUANGAN SYARIAH DI INDONESIA - Amalia, Euis; Al Arif, M. Nur Rianto (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
This study aims to analyze the potencies and roles of Universities both Islamic Higher Education (PTA) and Public Higher Education (PTU) in providing human resources through Islamic economic and finance learning development that accommodates the competencies of industries demand. The methods used in this study are the path analysis and the content analysis. Based on the Path analysis, it is found that there is a significant relationship between the academicians’ perception on the curriculum and learning model, and practitioners’ perception on human resource competencies for industries. In addition, the Paired T Test proves that there is no profile difference between the graduates of PTA and PTU; both have equal opportunities to meet the human resource demand of industries. Meanwhile, based on the content analysis toward the curriculum it is found that the learning system results in different competencies.